Coreografía de una matanza: memoria y performance de la masacre de Accomarca en el carnaval ayacuchano en Lima, Perú - Aroni, Renzo (Pontificia Universidad Católica del Perú. Fondo Editorial, 2015)
On August 14, 1985, during the long internal armed conflict between the Maoist guerrilla group Sendero Luminoso and the Peruvian state, an army patrol entered the Andean town Accomarca, located in the Ayacucho region, and killed 69 indigenous people, including children and elderly, alleged supporters of the insurgent group. The majority of survivors and relatives of victims were displaced to Lima and integrated into the victims’ organization and the Asociación Hijos del Distrito de Accomarca - AHIDA. Since 2011, on the occasion of the extradition from the United States of Lieutenant Telmo Hurtado, main person responsible of the massacre, the AHIDA has recreated the painful experience of the massacre through an annual Ayacuchan Carnival performance incor- porating choreography and testimonial songs to demand justice for the victims of the massacre. In addition, this carnivalesque performance involves children and young people who did not lived the massacre, but imagine, interpret and create their own memory by communicating with the survivors and participating in the cultural production of the event. In this article, I expose how survivors and relatives of victims remember the massacre and transmit their memories to their children through a carnivalesque performance. I describe the production of an intergenerational memory through the intergenerational transmission, which is constructed in the domestic space (family), the communal/institutional space (AHIDA), and the public space (Carnival). Surely, the occasion of the Carnival is a powerful spacefor the production of other forms of memory, and for the demand for justice through participatory choreographic and musical performance.

El 14 de agosto de 1985, durante el largo conflicto armado interno entre la guerrilla maoísta de Sendero Luminoso - SL y el Estado peruano, una patrulla del Ejército entró en el pueblo andino de Accomarca, ubicado en la región de Ayacucho, y asesinó a 69 personas indígenas, incluyendo niños y ancianos, supuestos simpatizantes del grupo insurgente. La mayoría de los sobrevivientes y familiares de las víctimas se desplazaron a Lima y se integraron en una organización de víctimas y en la Asociación Hijos del Distrito de Accomarca - AHIDA. Desde el año 2011, con motivo de la extradición desde los Estados Unidos del mayor Telmo Hurtado, principal responsable de la masacre, la AHIDA ha recreado la dolorosa experiencia de la matanza a través de una performance anual del carnaval ayacuchano, incorporando coreografías y canciones testimoniales para exigir la justicia para las víctimas de la masacre. Esta performance carnavalesca integra a los niños y jóvenes que no vivieron la masacre, pero imaginan, interpretan y crean su propia memoria mediante la comunicación con los sobrevivientes y la participación en la producción cultural del evento.En este artículo expongo cómo los sobrevivientes y familiares de las víctimas recuerdan la masacre y transmiten sus memorias a sus hijos a través de una actuación carnavalesca. Describo la producción deuna memoria intergeneracional a través de la transmisión intergeneracional, que se construye en el espacio doméstico (familia), el espacio comunal/institucional (AHIDA), y el espacio público (carnaval). Sin duda, la ocasión del carnaval es un espacio de gran alcance para la producción de otras formas de memoria, y para la demanda de la justicia a través de una coreografía participativa y performance musical.
Choreographing a Massacre: Memory and performance of the Accomarca Massacre in the Ayacuchan Carnival in Lima, Peru
Keywords: Antropología; https://purl.org/pe-repo/ocde/ford#5.04.03